Recommendations for Better Civic Learning: Building and Rebuilding Democracy - Jennings, Bruce (The Hastings Center report, 2021)
This is the concluding essay for a special report from The Hastings Center entitled Democracy in Crisis: Civic Learning and the Reconstruction of Common Purpose, which grew out of a project supported by the John S. and James L. Knight Foundation. This essay provides an integrative discussion of various theoretical and practical reform perspectives offered by other essays in the report. It also offers a number of recommendations. It notes that the aim of the special report is not to propose specific reform measures but, rather, to consider larger, more theoretic concerns related to political and economic questions, which are personal and structural—psychological, cultural, and institutional—at the same time. In response, this essay argues that the best relationship between the citizenry and government in a democracy is not one of deference, nor one of contestation, but one that is critically constructive, which in turn is linked to practices of civic learning. To be constructive, citizens need scientific literacy, an understanding of how government and other institutions work, critical thinking abilities, and many open and diverse forums for civic learning to offset the increasingly isolating media “bubbles” that are the only source of information for many. The essay then formulates five recommendations designed to facilitate critically constructive citizenship and civic learning. These are creating a basis for civic participation, acquiring information, talking to each other, designing institutional change, and achieving deliberation.